EKSISTENSI WANITA KARIR DALAM MENDUKUNG KEHARMONISAN RUMAH TANGGA: DI DESA GUNOSARI, KECAMATAN TLOGOSARI, KABUPATEN BONDOWOSO - Nurlaili; Amrotus Soviah (ASA, 2024)
This research focuses on examining the existence of career women in supporting family harmony. This research uses qualitative descriptive research. The research location is Gunosari Village, Tlogosari District, Bondowoso Regency. The basis for a career woman is education and personal desires. Meanwhile, the position of career women in households in Gunosari village is an emancipatory movement to support families in forming a harmonious household. The pattern for building a harmonious family is to apply time management, conflict management, emotional management and one-way mindset management while simultaneously giving in to each other, understanding and respecting each other.